Anatomical evaluation of the nasopalatine canal using CBCT (Cone Beam Computed Tomography): Method validation in open source software (Research, Society and Development, 2020)
Objective: Development and validation (using open source software) of a method for volumetric and linear assessment of the nasopalatine channel (NPC) using cone beam computed tomography (CBCT). Materials and methods: This was an observational, cross-sectional study of 276 CBCTs. Acquisition was performed on a Prexion 3D computerized tomography scanner (manufacturer), using voxels of 0.08 mm and 0.14 mm, (with FOV at 5 and 12 cm). The images were compiled and divided in accordance with gender and the dental condition of the maxilla. Evaluation took place on a MacBook Pro computer using the Horos Project program (Version 3.3.5). Linear measurements and NPC volumetric evaluations were performed after correcting the orientation axes (sagittal and axial). The length and ROI volume tools were used. Results: The average age for men was 60.15 ± 11.94, for women it was 59.95 ± 10.63. Respectively, for men and women, the average NPC volume values ​​ were: 68.59 mm3 and 59.37 mm3 (p = 0.032), for length they were 10.08 mm and 8.84 mm (p = 0.000). Of the dentate participants, the NPC averages for volume for men and women were: 71.01 mm3 and 57.18 mm3 (p = 0.007), for length they were 10.26 mm and 9.14 mm (p = 0.001). In the edentulous, the average NPC lengths were 9.79 mm (men) and 8.37 mm (women) (p = 0.005). Conclusion: For linear and volumetric nasopalatine channel assessment, the post-processing method used in the Horos software was considered precise and easy-to-use.